Analisis Keefektifan Pembelajaran Online di Masa Pandemi Covid 19 - Nisa, Nur Rohmatun (J-PGMI: Jurnal Pendidikan Guru MI, 2023)
The rapid advancement of technology and information greatly affects the development of education. One technology that plays a role in education is online learning. During the Covid pandemic that hit the world in education an online learning system was applied. This has led several schools to make changes in their learning systems. Of course, it is very influential on the effectiveness of learning. The purpose of this study was to analyze the effectiveness of online learning methods. This study uses a qualitative exploratory method and an inductive approach in its research. In this study, there were 8 resource persons from the MI Mazra'atul Ulum 01, which consisted of 3 teachers, 2 guardians, and 3 students. Information retrieval is carried out systematically consisting of questions that are compiled and then linked and developed with related literature. The results of this study indicate that (1) the lack of effectiveness is due to a lack of infrastructure (2) a massive lack of technology education (3) a lack of progressive socialization of the human resources involved.